THE EFFECT OF VOCABULARY LEARNING STRATEGIES ON VOCABULARY MASTERY BASED ON GENDER DIFFERENCES - Arina Afiyati Shadikah; Endang Fauziati; Slamet Supriyadi (Universitas Sebelas Maret, 2017)
There are lots of studies about vocabulary learning strategies used by EFL learners. In this recent study focuses on the effect of vocabulary learning strategies (VLSs) on learners’ vocabulary mastery. Nevertheless, in this study the subject were categorized based on gender (male and female). This study aims to identify the effect of vocabulary learning strategies employed by female and male learner at LBPP LIA Solo in learning new vocabularies on their vocabulary mastery. This qualitative study was a qualitative study proposed by Pawlak (2008). The participants of this research involved 10 male learners and 10 female learners of higher intermediate level at LBPP LIA Solo. The data were collected via vocabulary learning strategy questionnaaires (VLSQs), interview and test. The data collected were analyzed qualitatively. The research finding showed that female learner tend to use more vocabulary learning strategies than male did. In addition, the the more vocabulary learning strategies applied, the better effect they got in vocabulary mastery.